A new metal-organic framework with ultra-high surface area - Gruenker, Ronny; Bon, Volodymyr; Mueller, Philipp; Stoeck, Ulrich; Krause, Simon; Mueller, Uwe; Senkovska, Irena; Kaskel, Stefan (Chemical Communications, 2014)
A new mesoporous MOF, Zn4O(bpdc)(btctb)4/3 (DUT-32), containing linear ditopic (bpdc2−; 4,4′-biphenylenedicarboxylic acid) and tritopic (btctb3−; 4,4′,4′′-[benzene-1,3,5-triyltris(carbonylimino)]tris-benzoate) linkers, was synthesised. The highly porous solid has a total pore volume of 3.16 cm3 g−1 and a specific BET surface area of 6411 m2 g−1, adding this compound to the top ten porous materials with the highest BET surface area. © 2014 Royal Society of Chemistry.
CRIS-Team Scopus Importer:2023-03-20